Enhancement of productivity and nutrient content in pearl millet by agronomic fortification - Arokiamary, S; Vallal Kannan, S; Renuka, R; Sivakumar, T; Sangeetha, J V V (Plant Science Today, 2025)
Field level experiment was conducted at the Agricultural College and Research Institute, Madurai, Tamil Nadu Agricultural University (TNAU), India during the rabi season of 2022 and 2023. The objective was to develop a compendium technology to enhance iron (Fe) and zinc (Zn) content, enhance the yield in pearl millet through agronomic fortification using a Factorial Randomized Block Design. The study involved a bio-fortified hybrid (ICMH 1202) and CO 10 of TNAU variety, with three replications. The treatments included soil application of Zn in chemical and microbial forms, their combination and supplementation of Zn and Fe in chemical form through foliar with the combination of CO 10 and ICMH 1202. The results revealed that cultivation of CO 10 with ZnSO4 at 25 kg ha-1 (100 % recommended dose) applied to the soil, combined with foliar supplementation of 0.5 % of ZnSO4), 0.5 % of FeSO4 and nano-urea (@ 2 mL L-1 of water), in combination with other agronomic practices, achieved higher yield (3245 kg ha-1), net income (Rs. 42155 ha-1) and BCR of 2.18. This treatment also recorded Fe content of 119.85 ppm and Zn content of 39.29 ppm. Similarly, cultivation of ICMH 1202 under the same treatment achieved a yield of 2917 kg ha-1 and recorded higher Fe (178.11 ppm) and Zn (49.76 ppm) content in the grain. Increasing Zn and Fe application levels enhanced their total content in pearl millet grains. External application of Zn and Fe is essential for achieving optimal nutrient levels in bio-fortified hybrids, particularly under micronutrient-deficient soil conditions.